2014
DOI: 10.1002/bjs.9516
|View full text |Cite
|
Sign up to set email alerts
|

Early sac shrinkage predicts a low risk of late complications after endovascular aortic aneurysm repair

Abstract: BackgroundAneurysm shrinkage has been proposed as a marker of successful endovascular aneurysm repair (EVAR). Patients with early postoperative shrinkage may experience fewer subsequent complications, and consequently require less intensive surveillance.MethodsPatients undergoing EVAR from 2000 to 2011 at three vascular centres (in 2 countries), who had two imaging examinations (postoperative and after 6–18 months), were included. Maximum diameter, complications and secondary interventions during follow-up wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
82
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(85 citation statements)
references
References 19 publications
2
82
1
Order By: Relevance
“…This is an important fact as it has been shown that patients with major sac shrinkage have a very low risk of complications for up to 5 years. 35 The main limitation of our study was the low quality of the data because only case reports and one case cohort study exist in the literature. In addition, as these cases were executed in selected centers with profound laparoscopic expertise, the results with this method may not be generalized in daily practice.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This is an important fact as it has been shown that patients with major sac shrinkage have a very low risk of complications for up to 5 years. 35 The main limitation of our study was the low quality of the data because only case reports and one case cohort study exist in the literature. In addition, as these cases were executed in selected centers with profound laparoscopic expertise, the results with this method may not be generalized in daily practice.…”
Section: Discussionmentioning
confidence: 97%
“…It has been suggested that early change in sac diameter is a strong predictor of late outcome after EVAR. 35 One report suggested that IMA type II endoleak after EVAR may be predictable. 11 Thus, the incidence of IMA type II endoleaks was associated with a larger crosssectional area of the aortic lumen at the level of the IMA ostium before EVAR (P ¼ .001).…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15] The most serious consequence of type III endoleaks is repeat exposure of the aneurysm sac to direct arterial blood pressure with subsequent aneurysm sac enlargement and death from AAA rupture. Additionally, it has now been recognized that endograft uncoupling can obstruct aortic blood flow resulting in AAA thrombosis and lower extremity ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of any abnormality, the presence of sac shrinkage and the demonstration of adequate proximal and distal sealing zones on the 1 year follow up CTA, very few patients will experience an aneurysm related problem requiring correction. 17 Stratification of follow up may be done depending on the pre-operative anatomical features of the aneurysm and the extent to which the device's instructions for use are accurately followed. The adequacy of proximal and distal fixation together with the anatomical features of the aneurysm (angulation, tortuosity) may predict the likelihood of needing corrective intervention.…”
Section: Imaging Surveillance Programmes Following Evarmentioning
confidence: 99%